Genre crash: The case of online shopping. (December 2017) - Andersen, Thomas Hestbæk; van Leeuwen, Theo Jacob
Abstract: Departing from systemic-functional studies of the genre of face to face shopping, the paper provides a cartography of an online fashion shopping site, showing how it consists of an array of micro genres (themselves hybrids of genres such as advertisements, fashion spreads, lifestyle magazine articles and Instagram style social media photography) which can be navigated in different ways, yet always connect to purchase options. Multimodally, online fashion shopping entextualizes face to face fashion shopping and in the process transduces embodied modes of communication into text and image, relying a great deal more on language than its face to face equivalent.